Bioactive Sphingolipids, Complement Cascade, and Free Hemoglobin Levels in Stable Coronary Artery Disease and Acute Myocardial Infarction. (9th July 2018) - Jadczyk, T.; Baranski, K.; Syzdol, M.; Nabialek, E.; Wanha, W.; Kurzelowski, R.; Ratajczak, M. Z.; Kucia, M.; Dolegowska, B.; Niewczas, M.; Zejda, J.; Wojakowski, W.
Abstract : Background . Acute myocardial infarction (AMI) and coronary artery bypass graft (CABG) surgery are associated with a pathogen-free inflammatory response (sterile inflammation). Complement cascade (CC) and bioactive sphingolipids (BS) are postulated to be involved in this process. Aim . The aim of this study was to evaluate plasma levels of CC cleavage fragments (C3a, C5a, and C5b9), sphingosine (SP), sphingosine-1-phosphate (S1P), and free hemoglobin (fHb) in AMI patients treated with primary percutaneous coronary intervention (pPCI) and stable coronary artery disease (SCAD) undergoing CABG. Patients and Methods . The study enrolled 37 subjects (27 male) including 22 AMI patients, 7 CABG patients, and 8 healthy individuals as the control group (CTRL). In the AMI group, blood samples were collected at 5 time points (admission to hospital, 6, 12, 24, and 48 hours post pPCI) and 4 time points in the CABG group (6, 12, 24, and 48 hours post operation). SP and S1P concentrations were measured by high-performance liquid chromatography (HPLC). Analysis of C3a, C5a, and C5b9 levels was carried out using high-sensitivity ELISA and free hemoglobin by spectrophotometry. Results . The plasma levels of CC cleavage fragments (C3a and C5b9) were significantly higher, while those of SP and S1P were lower in patients undergoing CABG surgery in comparison to the AMI group. In both groups, levels of CC factors showed no significant changes within 48 hours of follow-up. Conversely, SP and S1P levels gradually decreased throughout 48 hours in the AMI group but remained stable after CABG. Moreover, the fHb concentration was significantly higher after 24 and 48 hours post pPCI compared to the corresponding postoperative time points. Additionally, the fHb concentrations increased between 12 and 48 hours after PCI in patients with AMI. Conclusions . Inflammatory response after AMI and CABG differed regarding the release of sphingolipids, free hemoglobin, and complement cascade cleavage fragments.